2020
DOI: 10.1038/s41598-020-76383-w
|View full text |Cite
|
Sign up to set email alerts
|

Guanabenz modulates microglia and macrophages during demyelination

Abstract: Multiple sclerosis (MS) is an autoimmune disease characterized by infiltration of peripheral immune cells into the central nervous system, demyelination, and neuronal damage. There is no cure for MS, but available disease-modifying therapies can lessen severity and delay progression. However, current therapies are suboptimal due to adverse effects. Here, we investigate how the FDA-approved antihypertensive drug, guanabenz, which has a favorable safety profile and was recently reported to enhance oligodendrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…Nevertheless, the enhancement of the ISR had no effect on remyelination in the absence of IFN-γ. This is consistent with a recent study that showed that guanabenz, a drug closely related to Sephin1 ( Das et al, 2015 ), did not improve remyelination in the non-inflammatory cuprizone model of demyelination ( Thompson and Tsirka, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the enhancement of the ISR had no effect on remyelination in the absence of IFN-γ. This is consistent with a recent study that showed that guanabenz, a drug closely related to Sephin1 ( Das et al, 2015 ), did not improve remyelination in the non-inflammatory cuprizone model of demyelination ( Thompson and Tsirka, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…This resulted in D = 0.15 and P = 0.04, thus detecting a small but significant shift in phagocytic activity, which can be seen by the rightward shift in the histogram, density curve, and ECDF. While not as large of an increase relative to that observed after GCM treatment, this result agrees with published literature (Wu et al, 2009;Scheraga et al, 2016;Caponegro et al, 2019;Thompson et al, 2020)…”
Section: Comparing Ks Test To Reported Methodssupporting
confidence: 93%
“…Microglia and astrocytes play a major role in the pathogenesis of MS and EAE [75]. Their activation and maturation are critical to disease development and progression [76] and ablation of microglia suppresses EAE development [77].…”
Section: Discussionmentioning
confidence: 99%